THE CORRELATION BETWEEN AGE AND ANXIETY AMONG PRIMIGRAVIDA MOTHERS FACING CHILDBIRTH AT REKSA WALUYA HOSPITAL IN MOJOKERTO - Dyah Siwi Hety; Citra Adityarini Safitri; Ika Yuni Susanti (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Anxiety is a psychological response commonly experienced by primigravida pregnant women as they prepare for their first childbirth. The mother’s age is one of the factors that influence her emotional maturity and level of anxiety.This study aims to analyze the relationship between age and anxiety levels among primigravid mothers at Reksowaluyo Hospital in Mojokerto.This study employed a correlational design with a cross-sectional approach. The sample consisted of 40 primigravid mothers selected using total sampling. The research instrument was an anxiety level questionnaire. Data analysis was performed using the Pearson Product-Moment correlation test. The results showed that the majority of respondents experienced mild anxiety, namely 27 respondents (67.5%). Statistical analysis revealed a correlation coefficient (r) of 0.568 with a significance level of p = 0.000 (p < 0.01).There is a significant, positive, and strong relationship between age and anxiety levels among primigravida mothers. As the age of mothers within the healthy reproductive period increases, anxiety levels tend to rise, indicating that factors such as cognitive maturity and expectations play a role in mothers’ perception of anxiety. It is recommended that healthcare providers provide personalized education and psychological support to help mothers adaptively manage their anxiety in preparation for childbirth